A novel method for CT dosimetry with a suspended phantom setup. (August 2017) - Longo, Mariaconcetta; Genovese, Elisabetta; Orlandi, Chiara; Donatiello, Salvatore; Cassano, Bartolomeo; Colajacomo, Mauro; Magistrelli, Andrea; Tomà, Paolo; Cannatà, Vittorio
Highlights: A new method for estimating Computed Tomography dosimetric indices is proposed. A prototype designed for suspending the detector/phantom system fixed at the CT isocenter is realized. The method allows the direct measurements of CT dosimetric indices in helical mode. A dedicated formalism based on the proposed suspended phantom setup was developed. Abstract: Purpose: This work presents a method for estimating CT dosimetric indices with a prototype designed for suspending the phantom/ion chamber system fixed at the CT isocenter. The purpose of this study was to validate the proposed methodology, which can be used to provide a direct assessment of dosimetric indices in helical scans. Methods: The method is based on a reference setup in which the measuring system for CT dosimetry is in a stationary configuration, i.e. not bound to the CT table, and on a mathematical formalism developed for the proposed reference system. The reliability of the method was demonstrated through a set of experimental measurements. Firstly, dosimetric indices were measured with the new method and compared with the indices obtained with the procedure currently used for CT dosimetry (measuring system bound to the CT table). Secondly, dosimetric indices measured with the new method were compared with those displayed on the CT console. Results: There is good agreement between the dosimetric indices obtained with the standard setup and those obtained with the suspended phantom setup, within the expected range of errors. The difference between dosimetric indices estimated with the proposed method and those displayed on the CT console is below 2%. Conclusions: The method enables CT dosimetry to be performed with the dose detector in a stationary longitudinal position thanks to the newly introduced suspended phantom setup. Using this approach, CT dose can be assessed for high pitch helical scans, acquisitions without complete tube rotation and for cases where dynamic collimation is used.